Professional Windows Phone 7 game development creating games using XNA Game Studio 4 - Williams, Chris G.; Clingerman, George W. (Wiley Pub., 2011)
Annotation
Keywords: Microsoft XNA (Computer file); Windows phone (Computer file); Video games -- Programming; Video games -- Design; Microsoft XNA (Computer software); Windows phone (Computer software); Jeux vidéo; Programmation; Jeux vidéo; Conception; GAMES; Video & Electronic; Computer games; Design; Video games; Programming; Windows Phone 7; XNA Game Studio 4.0; Computer games; Computer software